Evaluation of Arabic Language Learning Programs in Pekanbaru City - amrinuddin; Hakmi Wahyudi; Nurmalita (Universitas Islam Negeri Palopo, 2025)
This study uses evaluative research with a descriptive approach. The aim is to assess the effectiveness of the Arabic language learning program in Pekanbaru City based on the aspects of context, input, process, and product. In general, the evaluation of the Arabic language learning program at SMA IT As-Sajadah and MA Ponpes Durratul Ilmi Al Islami in Pekanbaru City is quite effective in terms of context, as reflected in how Arabic language learning at SMA IT As-Sajadah and MA Ponpes Durratul Ilmi Al Islami in Pekanbaru City is designed in accordance with the current needs of students. It is also effective in terms of input, as seen in how well the schools are prepared to facilitate the learning and teaching process at SMA IT As-Sajadah and MA Ponpes Durratul Ilmi Al Islami in Pekanbaru City, both in terms of teaching staff and the facilities and resources that have been prepared. However, it is less optimal in terms of process, as seen in the uneven abilities of students, both in terms of mastery of the material and practical Arabic language skills.